Predictive Factors for Recurrence Following Hemorrhoidectomy Using the LEONARDO Laser Technique - Jawad, Aseel; Ali, Raad; Alwan, Mohammed (Jordan Medical Journal, 2025)
Purpose: This study investigates the influence of various factors, including defecation habits, age, gender, and obesity, on the recurrence of hemorrhoids after treatment with the LEONARDO laser technique. Hemorrhoids, a prevalent anorectal condition, often require intervention ranging from conservative management to surgical procedures. Traditional hemorrhoidectomy is associated with postoperative pain and high recurrence rates, whereas the LEONARDO laser technique promises a safer and less invasive alternative. Methods: A comprehensive analysis was conducted on patients who underwent hemorrhoidectomy using the LEONARDO laser technique. The study focused on assessing the impact of several risk factors, such as defecation habits (with a particular emphasis on obstructive defecation syndrome), age, gender, and obesity, on the recurrence of hemorrhoids. Data were collected over a two-year follow-up period post-surgery. Results: The findings revealed a significant correlation between certain defecation habits, notably obstructive defecation syndrome, and an increased rate of hemorrhoid recurrence, especially in older female patients. The study also observed that other factors like age, gender, and obesity played a role in the recurrence rates, although the impact of defecation habits was more pronounced. Conclusions: The results of this study highlight the critical importance of considering individual defecation patterns, particularly obstructive defecation syndrome, in the management and prognosis of hemorrhoids post-LEONARDO laser treatment. These insights can guide clinicians in tailoring postoperative care and counseling to reduce recurrence rates and improve patient outcomes.